Prevalence of traditional eye medicine use and its associated factors among adult ophthalmic patients in Gondar region of Ethiopia in 2020 - Biruk Lelisa Eticha; Aragaw Kegne Assaye; Haile Woretaw Alemu (Taylor & Francis Group, 2023)
Abstract: Traditional medicines are commonly used throughout the world, especially in Africa. About 13.2-82.3% of the population uses traditional eye medicine. These are forms of biologically based therapies, practices, or partially processed agents that are applied to the eye or administered orally to achieve a desired ocular therapeutic effect. To determine the prevalence and associated factors of traditional eye medicine use among adult ophthalmic patients attending the University of Gondar Comprehensive Specialized Hospital-Tertiary Eye Care and Training Center, Northwest Ethiopia, 2020. A cross-sectional study within the hospital was conducted on 502 newly admitted adult ophthalmic patients who were selected by using a systemic random sampling method from August 15 to 21 October 2020. Of the total (502) subjects, 93.1% of subjects participated in the study. From the total participants, 22.31% (112) (95% confidence interval (CI: 19-26%)) used traditional eye medicine in the past two years. Positive family history of traditional eye medicine use (Adjusted odds ratio(AOR = 11.1(95% CI: 4.8-25.6)), availability of traditional healers (AOR = 3.7 (95% CI: 1.6-8.6)), residency in the rural (AOR = 24.9 (95% CI: 10.4-59.7)), family income of 300-1,500 adjusted odds ratio (AOR) = 6.6 (95% CI: 1.9-22.9)), and ≥ 6 months (AOR = 8.5 (95% CI: 3.02-23.7) were significantly associated with traditional eye medicine use The driving issues for using TEM were the availability and costs of modern medicine. The prevalence of TEM is higher than in the previous study conducted in Ethiopia.